2009
DOI: 10.1016/j.heares.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Transient gain adjustment in the inferior colliculus is serotonin- and calcium-dependent

Abstract: In the inferior colliculus (IC), a brief period of acoustic conditioning can transiently enhance evoked discharge rate. The cellular basis of this phenomenon was assessed with whole cell current-clamp recordings in a gerbil IC brain slice preparation. The current needed to elicit a single action potential was first established for each neuron. A 5s synaptic stimulus train was delivered to the lateral lemniscus (LL), and followed immediately by the initial current pulse to assess a change in postsynaptic gain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 75 publications
0
19
0
1
Order By: Relevance
“…In addition, our previous work and other studies have shown that central auditory neurons may adjust their gain in aged animals to compensate for diminished AN input [Parthasarathy et al, 2014, Kotak and Sanes, 2003, Miko and Sanes, 2009]. Hence, to account for age-related differences in central gain, we attempted to equate central neural activation in a separate test by matching EFR amplitudes in young and aged animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our previous work and other studies have shown that central auditory neurons may adjust their gain in aged animals to compensate for diminished AN input [Parthasarathy et al, 2014, Kotak and Sanes, 2003, Miko and Sanes, 2009]. Hence, to account for age-related differences in central gain, we attempted to equate central neural activation in a separate test by matching EFR amplitudes in young and aged animals.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we attempted to equate peripheral activation by adjusting sound levels in young animals to match to aged animals’ median tone 8 kHz ABR wave I amplitudes at 85 dB pSPL. In addition to age-related changes in the auditory periphery, gain of the central auditory system has also been reported to increase to compensate for reduced ANF activation in aging [Parthasarathy et al, 2014, Kotak and Sanes, 2003, Miko and Sanes, 2009]. Therefore, we attempted to match central population activation by matching the young EFRs to the median of the aged EFRs evoked by 100 % depth AM tones at 85 dB SPL.…”
Section: Introductionmentioning
confidence: 99%
“…More information regarding the actual pattern of synaptopathy seen with age will lead to a better refinement of the model to accurately reproduce the EFRs. Central processing changes in aging and other forms of hearing loss manifest as decreases in inhibition (Caspary et al 2008) as well as changes in excitation due to compensatory mechanisms reacting to the reduced peripheral input (Cui et al 2007;Miko and Sanes 2009). However, these compensatory mechanisms come at the cost of reduced synchrony of neural representations (Rabang et al 2012).…”
Section: Effects Of Aging In Processing Simultaneous Sam Tonesmentioning
confidence: 99%
“…1D). Blocking mGluRs with a non-specific antagonist MCPG increases the gain in action potential firing of IC neurons (Miko and Sanes, 2009). Antagonism but not activation of group II mGluRs also increases firing of IC neurons in vivo (Voytenko and Galazyuk, 2011), suggesting suppression of cellular excitability by endogenous activity of group II mGluRs.…”
Section: Anatomy and Physiology Of Mglurs In Mammalian Auditory Midbrainmentioning
confidence: 99%